Association of APEX1 and OGG1 gene polymorphisms with breast cancer risk among Han women in the Gansu Province of China - Tao Wang; Haitao Wang; Suisheng Yang; Hongyun Guo; Binming Zhang; Huan Guo; Lan Wang; Gongjian Zhu; Yongdong Zhang; Haihong Zhou; Xiuli Zhang; Haining Li; et al. (BMC, 2018)
Abstract Background Genetic variations in key DNA repair genes may influence DNA repair capacity, DNA damage and breast carcinogenesis. The current study aimed to estimate the association of APEX1 and OGG1 polymorphisms with the risk of breast cancer development. Methods A total of 518 patients with histopathologically confirmed breast cancer and 921 region- and age-matched cancer-free controls were genotyped for the APEX1 polymorphisms rs3136817 and rs1130409 and the OGG1 polymorphisms rs1052133 and rs2072668 using a QuantStudio™ 12 K Flex Real-Time PCR System. Results The rs3136817 heterozygous TC genotype along with the rs3136817 dominant model (TC + CC) was strongly associated with breast cancer susceptibility (odds ratio [OR] = 0.670, 95% confidence interval [95% CI]: 0.513 - 0.873, P = 0.003; OR = 0.682, 95% CI: 0.526 - 0.883, P = 0.004, respectively). No significant associations were observed among rs1130409, rs1052133, rs2072668 and breast cancer risk. Furthermore, an allele combination analysis revealed that APEX1 haplotypes containing C-T (alleles rs3136817 and rs1130409) conferred a significantly lower risk (corrected P < 0.001). Conclusion This research is the latest report showing that an APEX1 rs3136817 heterozygous genotype may have a positive influence on DNA repair capacity in patients with breast cancer and thus may have a potential protective effect for Chinese Han women.